The Effectiveness of Islamic Religious Education Learning for Elementary School Students - Nurmar Atus; Raehang; Rahmawati (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
This research aims: 1) what is the effectiveness of islamic religious education learning for students at SD Negeri 1 Ranomeeto, South Konawe Regency And 2) what factors support and hinder the effectiveness of learning Islamic Religious Education for students at SD Negeri 1 Ranomeeto, South Konawe Regency. This research uses qualitative methods into primary data and secondary data. The data collection method cansists of interviews, obsevation and documentation which are the analyzed by means of data reducation, data presentation and drawing conclusions. Checking the validity of the data is carried out by extending observations, increasing persistence and triangulation. Based on yhe results of the research congducted, it shows that the effectiveness of learning Islamic religious education for students at SD Negeri 1 Ranomeeto can be know fromthe results of observations, interviews and documentation. The Islamic Religious Education Learning process is effective. Supporting factors and inhibiting factors are supporting factors for students, teachers, facilities and infrastructure. Obstacle factors. Students’ learning interst and learning behavior.